Clinical Significance of Haplo-Fever and Cytokine Profiling After Graft Infusion in Allogeneic Stem Cell Transplantation From Haplo-Identical Donors - Wang, Lining; Dai, Bo; Gao, Wenhui; Wang, Jing; Wan, Ming; Wang, Runshu; Wang, Ling; Jiang, Jieling; Blaise, Didier; Hu, Jiong (Frontiers in Medicine, 2022)
Allogeneic stem cell transplantation from haplo-identical donors (haplo-HSCT) has become a well established therapeutic option for hematological malignancies. Fever of unknown origin (haplo fever) early after the infusion of T cell repleted graft, which returned to normal right after post-transplantation cyclophosphamide (PTCy), is a unique clinical feature in patients undergoing haplo-HSCT. In the current study, the characteristics of haplo-fever and cytokine profiles during haplo-fever were retrospectively analyzed in a cohort of 37 patients undergoing T cell repleted haplo HSCT with PTCy as graft versus host disease (GvHD) prophylaxis. Thirty-three patients (89.2%) developed haplo-fever from day 0 to day +7. Patients with high peak temperatures tended to have a lower incidence of chronic GvHD (cGvHD) (p = 0.07), moderate to severe cGvHD (p = 0.08), and superior GvHD and relapse-free survival (GRFS, p = 0.04). During the haplo-fever there were significant increases in multiple cytokines including interferon gamma, interleukin (IL) 6, IL2, IL2 receptor, IL6, IL8, IL10, IL17, and tumor necrosis factor (TNF). The increases in IL2 receptor (p = 0.037) and TNF (p < 0.001) on day +4 were correlated with lower risk of cGvHD. Increased TNF > 1.8055-fold on day +4 was the best predictive threshold for cGvHD, and was correlated with a lower incidence of cGvHD (p < 0.001), moderate to severe cGvHD (p = 0.003), and superior GRFS (p < 0.001). These observations may reflect the early reactivation of donor T cells after haplo graft infusion, which would potentially be eliminated by PTCy. Further studies with larger independent cohorts of patients are warranted, to clarify the clinical significance of haplo-fever, and day +4 TNF as a potential biomarker to predict GvHD and GRFS.